The Influence of Experiental Marketing on Repurchase Intention and Customer Satisfaction of Restaurants in Surabaya (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This research seeks to examine the impact of experiential marketing on customer satisfaction, its effect on repurchase intention, and the role of customer satisfaction in influencing repurchase intention among patrons of Resto All You Can Eat Surabaya. The study applies a survey approach, gathering data through questionnaires distributed to selected samples from the population. The analysis is conducted using the Partial Least Square method. The findings reveal that experiential marketing significantly influences customer satisfaction at Resto All You Can Eat Surabaya. This indicates that when elements of experiential marketing—such as sensory experiences, emotional responses, creative cognitive stimulation, physical engagement, lifestyle alignment, and social identity—are enhanced, customer demand also increases. Moreover, experiential marketing is shown to affect customers’ repurchase intention. In other words, the stronger the customers’ experience in terms of sensory, affective, cognitive, physical, lifestyle, and social identity aspects, the greater their willingness to make repeat purchases. Finally, customer satisfaction itself plays a crucial role in driving repurchase intention. When satisfaction is reflected in positive feelings, verbal appreciation, enjoyment, and fulfillment during the purchasing process, customers are more inclined to return and buy again at the restaurant. These results suggest that Resto All You Can Eat Surabaya—and similar businesses—should strategically invest in strengthening experiential marketing elements as a core part of their customer relationship and retention efforts. By creating memorable and meaningful dining experiences that engage customers on multiple levels, the restaurant can foster stronger emotional connections, increase satisfaction, and encourage long-term loyalty. Practical implementations may include improving ambiance, offering interactive dining elements, training staff to provide personalized service, and leveraging social media to enhance community and identity among patrons.